2000
DOI: 10.1103/physrevlett.85.5170
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Charge Stripes in Cupric Oxide

Abstract: One of the present intensive concerns about the high-temperature superconductors is whether charge stripes are a key to superconductivity. Here we report observation of charge stripes in the simplest copper oxide, CuO, by real-space images obtained by electron microscopy. Charge-ordered domains and normal-lattice domains exist alternatively in the vapor-grown single crystal of CuO. Since CuO consists of the Cu-O bonding, which is a basic material feature for high- T(c) cuprates, the discovery of charge stripes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(115 citation statements)
references
References 37 publications
1
112
1
1
Order By: Relevance
“…When performing the first annealing step at 200°C under argon flow, the spectrum of Fig. 1͑a͒ shows a frequency triplet that reveals only one axially symmetric EFG 1 rameterized by italic values in Table I. The lower Q value could possibly be explained by an extra elongation of the average mercury-apical oxygen bond distance, d͓O͑2͒-Hg͔, upon fluorine doping, as observed in neutron diffraction data.…”
Section: A Experimentsmentioning
confidence: 79%
See 1 more Smart Citation
“…When performing the first annealing step at 200°C under argon flow, the spectrum of Fig. 1͑a͒ shows a frequency triplet that reveals only one axially symmetric EFG 1 rameterized by italic values in Table I. The lower Q value could possibly be explained by an extra elongation of the average mercury-apical oxygen bond distance, d͓O͑2͒-Hg͔, upon fluorine doping, as observed in neutron diffraction data.…”
Section: A Experimentsmentioning
confidence: 79%
“…In fact, numerous and complex structural distortions as polaron deformations, as well as charge and spin stripes, strongly dependent on ionic doping, have been reported in the high-T c copper oxides. In this context, the findings of spin and charge inhomogeneities in the CuO bonds 1 and the CuO 2 ͑Ref. 2͒ layers in YBa 2 Cu 3 O 6+␦ have been related to lattice deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Cupric oxide, on the contrary, is monoclinic, ferroelectric [18] and recent studies seem to indicate it possesses at least three different magnetic polymorphs [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…There are four molecular units in the crystallographic unit cell but only two in the primitive cell. The lattice constants are a = 4.69 Å, b = 3.42 Å, c = 5.13 Å and β = 99.58° [7]. Correlating the site symmetries with the C 2h factor group theory, the normal modes Γ ≡ 4A u +5B u +A g +2B g of the zone center are obtained.…”
Section: Structure and Symmetriesmentioning
confidence: 99%
“…Zheng et al found hole ordering in striped domains analogous to the charge stripes in cuprates [7], and further found that there exists a strong charge-spin-lattice coupling and a possible Cu orbital coupling contributing to the short-range antiferromagnetic interaction up to 800 K, where a charge-spin-lattice correlated phase transition featured by charge excitation, specific heat anomaly and decrease in lattice distortion was verified [8]. They also observed ferroelectric properties in this strongly magnetic-dielectric coupled material [9].…”
Section: Introductionmentioning
confidence: 99%